Breast cancer biologic and etiologic heterogeneity by young age and menopausal status in the Carolina Breast Cancer Study: a case-control study. Issue 1 (December 2016) - Chollet-Hinton, Lynn; Anders, Carey; Tse, Chiu-Kit; Bell, Mary; Yang, Yang; Carey, Lisa; Olshan, Andrew; Troester, Melissa
Abstract Background Young-onset breast cancer (<40 years) is associated with worse prognosis and higher mortality. Breast cancer risk factors may contribute to distinct tumor biology and distinct age at onset, but understanding of these relationships has been hampered by limited representation of young women in epidemiologic studies and may be confounded by menopausal status. Methods We examined tumor characteristics and epidemiologic risk factors associated with premenopausal women's and young women's breast cancer in phases I–III of the Carolina Breast Cancer Study (5309 cases, 2022 control subjects). Unconditional logistic regression was used to assess heterogeneity by age (<40 vs. ≥40 years) and menopausal status. Results In both premenopausal and postmenopausal strata, younger women had more aggressive disease, including higher stage, hormone receptor-negative, disease as well as increased frequency of basal-like subtypes, lymph node positivity, and larger tumors. Higher waist-to-hip ratio was associated with reduced breast cancer risk among young women but with elevated risk among older women. Parity was associated with increased risk among young women and reduced risk among older women, while breastfeeding was more strongly protective for young women. Longer time since last birth was protective for older women but not for young women. In comparison, when we stratified by age, menopausal status was not associated with distinct risk factor or tumor characteristic profiles, except for progesterone receptor status, which was more commonly positive among premenopausal women. Conclusions Age is a key predictor of breast cancer biologic and etiologic heterogeneity and may be a stronger determinant of heterogeneity than menopausal status. Young women's breast cancer appears to be etiologically and biologically distinct from that among older women.